Politik Impunitas dan Stagnasi Akuntabilitas Konstitusional di Indonesia: Suatu Analisis Hukum Tata Negara - Muchlis Sadzili; Yusdiyanto Yusdiyanto; Muhtadi Muhtadi (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The persistence of unresolved gross human rights violations in Indonesia reflects a deeper structural problem within the constitutional system, where legal accountability mechanisms remain weak and vulnerable to political intervention. This condition has enabled the emergence and consolidation of a politics of impunity, further reinforced by state-sponsored symbolic practices that normalize authoritarian legacies and erode public demands for justice. This study aims to analyze how the politics of impunity is formed and reproduced within Indonesia’s constitutional framework and to examine the role of symbolic state practices in sustaining the stagnation of constitutional accountability for gross human rights violations. Methodologically, this research employs a normative juridical type of research using constitutional law and socio-legal approaches. The unit of analysis includes constitutional norms, statutory regulations, judicial decisions, state policies, and symbolic practices related to human rights accountability. The study utilizes secondary data obtained through documentary and literature-based research, including legislation, court rulings, official state narratives, academic writings, and reports from human rights institutions. Data are analyzed through qualitative normative analysis, complemented by critical discourse analysis to assess the interaction between legal structures and symbolic narratives. The findings reveal that impunity is reproduced through stalled legal processes, weak institutional independence of human rights bodies, and the dominance of political calculations in state decision-making. Additionally, symbolic practices such as the legitimization of authoritarian figures contribute to the preservation of impunity by obscuring collective memory, reducing the urgency of accountability, and weakening constitutionalism in Indonesia’s democratic order.